A Note on Restaurant Pricing and Other Examples of Social Influences on Price - Becker, Gary S. (Journal of Political Economy, 1991)
This note tries to explain why many successful restaurants, plays, sporting events, and other activities do not raise prices even with persistent excess demand. The authors approach assumes that demand by a typical consumer is positively related to quantities demanded by other consumers. This can explain not only the puzzle about prices, but also why consumer demand is often fickle, why it is much easier to go from being "in" to being "out" than from "out" to "in," and why supply does not increase to reduce the excess demand. Copyright 1991 by University of Chicago Press.